Keadilan Pemilu Dalam Penanganan Bawaslu Sulawesi Tenggara Laporan Ijazah Palsu Calon Legislatif Kota Kendari - Mpesau, Alasman; Ruslan, Ruslan; Rosidin, Ayib (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2026)
This study examines the handling of reports concerning the use of a fake diploma by a legislative candidate in Kendari City by the Election Supervisory Agency of Southeast Sulawesi (Bawaslu Sultra), which concluded that the case did not fulfill the elements of an electoral crime, despite official evidence from the Ministry of Education stating that the reported individual was not registered as a National Examination participant. This finding contrasts with the investigation conducted by the Kendari City Police, which designated the reported individual as a suspect in a general criminal offense. The purpose of this study is to analyze the implementation of the electoral justice system by Bawaslu Sultra in handling electoral criminal violations and to examine whether the process reflects the principles of electoral justice. This research employs an empirical normative method using statutory, conceptual, and field investigation approaches. The findings indicate that the electoral justice system within Bawaslu Sultra functioned procedurally; however, the outcome did not reflect substantive justice. The dominance of Bawaslu within the Integrated Law Enforcement Center (Sentra Gakkumdu), without the active involvement of the Police and the Prosecutor’s Office in plenary decision-making, creates potential opportunities for abuse of authority by Bawaslu. Therefore, future enforcement of electoral criminal law should strengthen the role of the Police in investigations through more functional cooperation within Sentra Gakkumdu.